Effect of alternating current on the performance of magnesium sacrificial anode. (5th March 2016) - Tang, Dezhi; Du, Yanxia; Li, Xiaxi; Liang, Yi; Lu, Minxu
Abstract: Performance of magnesium sacrificial anode under alternating current was investigated in 4 g/L Na2 SO4 simulated backfill solution by weight-loss measurements for 96 h, electrochemical measurements and surface examination. Alternating current increased the dissolution of magnesium, and at the same time, its DC potential shifted positively. The output cathodic protection current decreased at alternating current density of 50 A/m 2 . Polarity reversal occurred to magnesium sacrificial anode as soon as alternating current interference of 100 A/m 2 (or larger) was applied. Besides the "instant effect", the polarity reversal showed a "time effect". It disappeared gradually at alternating current density of 100 A/m 2 . When alternating current density was more than 200 A/m 2, the polarity reversal remained throughout the experiment (96 h). Based on the results of electrochemical measurements and surface examination, mechanism of polarity reversal was proposed. Graphical abstract: Highlights: Mg could not provide enough protection to carbon steel with AC ≥ 100 A/m 2 . Polarity reversal occurred to Mg as soon as AC of 100 A/m 2 (or larger) was applied. The polarity reversal of Mg exhibited a "time effect" under AC. Both AC oscillation and varied polarizations contributed to the polarity reversal of Mg.